Fiscal Policy, State Building and Economic Development. (13th March 2018) - Addison, Tony; Niño‐Zarazúa, Miguel; Pirttilä, Jukka
Abstract: This article presents a synopsis of the contextual conditions, factors and challenges under which the recent evolution of tax systems has taken place, as an introduction to this United Nations University‐World Institute for Development Economics Research Special Issue. The article, as the studies in this collection, gives especial emphasis to the role natural endowments, political economy, social structure and history, and the interplay between politics and tax revenues. These are relevant issues, considering that the Millennium Development Goals and now the Sustainable Development Goals have placed fiscal policy, and tax policy and revenue mobilisation in particular, at the centre of national and international development efforts. Delivering on the Sustainable Development Goals will require a level of state revenue mobilisation capacity in many ways unprecedented in the history of development policy. © 2018 UNU‐WIDER. Journal of International Development published by John Wiley & Sons, Ltd.